Degree of Monotone Approximation in , p LÎ± Spaces - Shamkhi, I. Z.; Jassim, S. K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The aim of this paper is to study the best approximation of unbounded functions in the weighted spaces,1, 0 ,pp L Î±Î± â‰¥>.Key Words: Weighted space, unbounded functions, monotone approximation